Power Quality Assessment of Distributed Generator Grounding Method - Sutherland, P.E.; Short, T.A. (IEEE transactions on industry applications, 2009)
The objective of this project was to assess the specific transformer grounding and connection methods that are used at the subject utility for distributed generators (DGs) and provide a risk assessment in terms of potential impact, ways to minimize the impact, and site specific screening criteria for additional protection that may be required for DG interconnection. The utility has standardized on a grounded wye-grounded wye transformer connection for customers connected to their distribution system. When a backup generator exists in the customer's facility that could be paralleled with the utility system, a contactor is installed on the neutral to ground connection on the generator. This contactor is opened at any time that the generator is paralleled. The utility is considering remotely dispatching these distributed generation assets in times of peak load in the future. This will require the generators to run paralleled for extended periods of time. Grounding practices for auxiliary generators were evaluated, and simulations of both steady-state and fault conditions were conducted. The most critical factors were found to be assuring that the generator ground switch was closed during islanding and that the overvoltage protection operates correctly to isolate the generator during fault conditions. Recommendations for overvoltage protection and testing were developed based upon the results.